Production process for synchronously improving profile tolerance of two sides of copper foil and product and application thereof

By controlling the polishing time of the cathode roller and the electrolyte composition, the problem of synergistic improvement of the roughness of the copper foil and the glossy surface is solved, and copper foil with high strength, high ductility and stability is prepared for the manufacture of buried copper foil and PCB. , meets the performance requirements of modern electronic products.

CN119121331AActive Publication Date: 2024-12-13ZHEJIANG GARDEN NEW ENERGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411186969.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2024-12-13
Estimated Expiration
2044-08-28

AI Technical Summary

Technical Problem

The prior art is difficult to improve the roughness of the breasted and glossy surface of copper foil at the same time, resulting in insufficient signal transmission efficiency and etching corrosion resistance in PCB manufacturing, and it is difficult to meet the comprehensive performance requirements of modern electronic products for conductive materials.

Method used

In the copper foil production process, the online polishing time of the cathode roller and the flow rate of the aqueous hydroxyethyl cellulose solution and collagen solution in the electrolyte are accurately adjusted, and a matte surface roughness MRz≤2.5μm and gloss roughness SRz≥ were prepared to satisfy the roughness MRz≤2.5μm and the smooth surface roughness SRz≥ 1.3μm electrolytic copper foil combined with optimized copper sulfate electrolyte composition and process conditions.

Benefits of technology

The high strength and high ductility of copper foil are achieved, ensuring the smooth side corrosion of the buried copper foil and the stability of the breast profile direction, and meeting the strict requirements of modern electronic products for conductive materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121331A_ABST
    Figure CN119121331A_ABST
Patent Text Reader

Abstract

The invention discloses a production process for synchronously improving the profile tolerance of two sides of a copper foil, which comprises the following steps: injecting an electrolyte into an electrolytic bath with a cathode roller through a liquid separation valve, then injecting a hydroxyethyl cellulose aqueous solution and a collagen aqueous solution which are respectively prepared into the electrolytic bath, and preparing the copper foil after electrolysis, the injection flow of the hydroxyethyl cellulose aqueous solution is 11 + / -2L / h; the injection flow of the collagen aqueous solution is 8 + / -2L / h; and the cathode roller is subjected to online polishing treatment before electrolysis, and the polishing time is 45-70 min. According to the production process disclosed by the invention, the rough surface roughness of the copper foil is controlled while the smooth surface roughness is controlled, the electrolytic copper foil special for the buried resistance copper foil is prepared, and the performance requirements that the rough surface roughness MRz is smaller than or equal to 2.5 microns, the smooth surface roughness SRz is larger than or equal to 1.3 microns, the tensile strength is larger than or equal to 360 N / mm < 2 >, and the ductility is larger than or equal to 6% are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electronic material processing, and specifically relates to a production process for simultaneously improving the double-sided contour of copper foil and its product and its application in preparing buried copper foil and further preparing PCB. Background Art

[0002] In the electronics industry, buried copper foil is widely used in the manufacturing process of printed circuit boards (PCBs). Buried copper foil has good conductivity and mechanical strength and can be used to connect different layers on a circuit board. With the rapid development of communication technology, the Internet of Things and Internet technology, electronic products are gradually becoming smaller, thinner, smarter and more multifunctional. Buried copper foil, as a special conductive material, has unique advantages in meeting these requirements. It can achieve precise control of current transmission by PCB by controlling the resistance value, thereby ensuring the stability and reliability of the circuit.

[0003] However, the above applications have put forward more stringent requirements on the comprehensive performance of resistor copper foil. Resistor copper foil not only needs to have low roughness on the matte surface to ensure efficient signal transmission, but also needs to have high roughness on the glossy surface to ensure more stable corrosion resistance in downstream processing and etching. However, achieving the synergistic improvement of the two is a very challenging task. Summary of the invention

[0004] In view of the above problems, the present invention discloses a production process for simultaneously improving the double-sided profile of copper foil, which controls the roughness of the matte surface of the copper foil while controlling the roughness of the smooth surface, so as to obtain an electrolytic copper foil specially used for buried copper foil, which satisfies the requirements of the roughness of the matte surface MRz≤2.5μm, the roughness of the smooth surface SRz≥1.3μm, and the tensile strength ≥360N / mm 2 , performance requirement of elongation ≥6%.

[0005] To achieve the above purpose, the specific technical solution of the present invention is as follows:

[0006] A production process for simultaneously improving the double-sided profile of copper foil comprises the following steps:

[0007] The copper sulfate electrolyte is injected into an electrolytic cell with a cathode roller, and then the prepared hydroxyethyl cellulose aqueous solution and collagen aqueous solution are injected into the electrolytic cell, and the copper foil is prepared after electrolysis;

[0008] The concentration of the hydroxyethyl cellulose aqueous solution is 1.0±0.5 g / L, and the injection flow rate is 11±2 L / h;

[0009] The concentration of the collagen aqueous solution is 1.5±0.5 g / L, and the injection flow rate is 8±2 L / h;

[0010] Before electrolysis, the cathode roller is polished online for 45 to 70 minutes.

[0011] The production process disclosed in the present invention achieves the effect of synchronously improving the double-sided profile of the copper foil by precisely controlling the polishing time of the cathode roller online polishing treatment and the flow rates of the hydroxyethyl cellulose aqueous solution and the collagen aqueous solution added to the electrolyte, thereby reducing the roughness of the matte surface (controlling MRz≤2.5μm) while improving the roughness of the smooth surface (controlling SRz≥1.3μm), and ensuring the high strength and high ductility of the copper foil (tensile strength≥360N / mm 2 , elongation ≥6%).

[0012] It has been found through experiments that if the polishing time is not appropriate, or the flow rates of the added hydroxyethyl cellulose aqueous solution and the collagen aqueous solution are too large or too small, the prepared copper foil cannot meet the above performance requirements.

[0013] The copper sulfate electrolyte is prepared by adding copper wire with a diameter of 8 mm (copper purity ≥ 99.95%), sulfuric acid with a concentration of 98%, pure water, etc.

[0014] Preferred:

[0015] The copper sulfate electrolyte has a copper ion concentration of 83.5±15 g / L and H 2 SO 4 The concentration is 130±20g / L, and the chloride ion concentration is 5~25ppm;

[0016] Further preferably, in the copper sulfate electrolyte, the copper ion concentration is 83.5±5g / L, H 2 SO 4 The concentration is 130±10g / L, and the chloride ion concentration is 5~15ppm.

[0017] Preferred:

[0018] The molecular weight of the collagen used in the collagen aqueous solution is not higher than 5000D; more preferably, it is not higher than 3000D, and more preferably, it is 1000-3000D.

[0019] The online polishing process is performed using a polishing brush;

[0020] Preferred:

[0021] The mesh number of the polishing brush is 1200±500 mesh, the rotation speed is 220±30r / min, and the swing speed is 160±30 times / min;

[0022] The pressure current of online polishing is 0.4±0.3A, and the rotation speed of the cathode roller is 2.2±0.5m / min.

[0023] The electrolysis is preferably:

[0024] The upper liquid temperature is 51±3℃, and the upper liquid flow rate is 43±5m 3 / h;

[0025] The current intensity is 45000±5000A, and the cathode roller speed is 4.721±0.7m / min.

[0026] It has been found through experiments that the upper liquid temperature will also affect the performance of the prepared electrolytic copper foil. Therefore, the upper liquid temperature needs to be stabilized at 51±3℃.

[0027] The invention also discloses an electrolytic copper foil prepared according to the process, and uses the copper foil to prepare buried barrier copper foil, which is further applied to PCB.

[0028] The copper foil has a tensile strength of ≥360N / mm 2 , elongation ≥ 6%, MRz ≤ 2.5μm, SRz ≥ 1.3μm.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The present invention proposes a production process for simultaneously improving the double-sided profile of copper foil. By precisely controlling the polishing time of the cathode roller online polishing treatment and the flow rates of the hydroxyethyl cellulose aqueous solution and the collagen aqueous solution added to the electrolyte, the roughness of the rough surface of the copper foil is controlled while the roughness of the smooth surface is controlled, so as to obtain an electrolytic copper foil specially used for buried copper foil. The smooth surface roughness SRZ ≥ 1.3 μm and the rough surface low roughness MRZ ≤ 2.5 μm are provided. It has strong practicality in improving the side corrosion of the smooth surface of the buried barrier layer and reducing the rough surface profile of the buried barrier copper foil, and realizes more stable use in the preparation of buried barrier copper foil. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The SEM images of the smooth surface (S surface) and the matte surface (M surface) of the copper foil prepared in Example 1;

[0032] Figure 2 The SEM images of the smooth surface (S surface) and the matte surface (M surface) of the copper foil prepared in Example 2;

[0033] Figure 3 The SEM images of the smooth surface (S surface) and the matte surface (M surface) of the copper foil prepared in Example 3;

[0034] Figure 4 The SEM images of the smooth surface (S surface) and the matte surface (M surface) of the copper foil prepared in Example 4;

[0035] Figure 5 The SEM images of the smooth surface (S surface) and the matte surface (M surface) of the copper foil prepared in Example 5;

[0036] Figure 6 The SEM images of the smooth surface (S surface) and matte surface (M surface) of the copper foil prepared in Comparative Example 1;

[0037] Figure 7 The SEM images of the smooth surface (S surface) and matte surface (M surface) of the copper foil prepared in Comparative Example 2;

[0038] Figure 8 The SEM images of the smooth surface (S surface) and matte surface (M surface) of the copper foil prepared in Comparative Example 3;

[0039] Fig. 9 The SEM images of the smooth surface (S surface) and matte surface (M surface) of the copper foil prepared in Comparative Example 4;

[0040] Fig.10 The SEM images of the smooth surface (S surface) and the matte surface (M surface) of the copper foil prepared in Comparative Example 5;

[0041] Fig.11 These are SEM images of the smooth side (S side) and matte side (M side) of the copper foil prepared in Comparative Example 6. DETAILED DESCRIPTION

[0042] The present invention is further described in detail below in conjunction with examples and comparative examples, but the embodiments of the present invention are not limited thereto. The specific implementation methods described herein are only for illustrating and explaining the present invention and are not intended to limit the scope of protection of the present invention.

[0043] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0044] Example 1

[0045] (1) Add 8mm diameter copper wire (copper purity ≥ 99.95wt%), 98wt% sulfuric acid, pure water, etc. into the copper dissolving tank;

[0046] (2) Adjust the required ion concentrations of the copper sulfate electrolyte in the clean liquid tank: copper ions 85g / L, H 2 SO 4 The concentration is controlled at 130g / L, and the chloride ion concentration is controlled at 10ppm;

[0047] (3) Add hydroxyethyl cellulose, collagen (molecular weight 3000D), and 2 kg of wood powder activated carbon into the waste liquid tank and circulate for 2 h;

[0048] (4) injecting the electrolyte into the electrolytic cell with the cathode roller through the liquid separator valve, introducing the prepared hydroxyethyl cellulose aqueous solution with a concentration of 1.0 g / L and adjusting the flow rate to 9 L / h; introducing the collagen aqueous solution with a concentration of 1.5 g / L and adjusting the flow rate to 8 L / h;

[0049] (5) Use a plate heat exchanger to adjust and maintain the temperature of the upper liquid to 50°C; at the same time, adjust the upper liquid flow rate to 43m by controlling the upper liquid valve. 3 / h level;

[0050] (6) Use a polishing brush with a mesh size of 1200 to polish the surface of the cathode roller online, set the polishing brush speed to 220 r / min, the swing speed to 160±30 times / min, the polishing pressure current to 0.3A, the cathode roller speed to 1.100 m / min, and the polishing time to 60 min;

[0051] (7) After polishing, the current intensity was set to 45000A and the cathode roller speed was set to 4.721 m / min for electrolysis;

[0052] (8) After electrolysis is completed, the electrolytic copper foil is peeled off from the cathode roller by a stripping roller after pickling.

[0053] The data of the electrolytic copper foil prepared in this example are shown in Table 1.

[0054] Example 2

[0055] (1) Add 8mm diameter copper wire (copper purity ≥ 99.95%), 98% sulfuric acid, pure water, etc. into the copper dissolving tank;

[0056] (2) Adjust the required ion concentrations of the electrolyte in the clean liquid tank: copper ion 80g / L, H 2 SO 4 The concentration is controlled at 128g / L, and the chloride ion concentration is controlled at 9ppm;

[0057] (3) Add hydroxyethyl cellulose, collagen (molecular weight 3000D), and 2 kg of wood powder activated carbon into the waste liquid tank and circulate for 2 h;

[0058] (4) injecting the electrolyte into the electrolytic cell with the cathode roller through the liquid separator valve, introducing the prepared hydroxyethyl cellulose aqueous solution with a concentration of 1.0 g / L and adjusting the flow rate to 13 L / h; introducing the collagen aqueous solution with a concentration of 1.5 g / L and adjusting the flow rate to 10 L / h;

[0059] (5) Use a plate heat exchanger to adjust and maintain the temperature of the upper liquid to 54°C; at the same time, adjust the upper liquid flow rate to 44m by controlling the upper liquid valve. 3 / h level;

[0060] (6) Use a polishing brush with a mesh size of 1200 to polish the surface of the cathode roller online, set the polishing brush speed to 230 r / min, the swing speed to 160±30 times / min, the polishing current to 0.3 A, the cathode roller speed to 1.100 m / min, and the polishing time to 65 min;

[0061] (7) After polishing, the current intensity was set to 43000A and the cathode roller speed was set to 4.426 m / min for electrolysis;

[0062] (8) After electrolysis is completed, the electrolytic copper foil is peeled off from the cathode roller by a stripping roller after pickling.

[0063] The data of the electrolytic copper foil prepared in this example are shown in Table 1.

[0064] Example 3

[0065] (1) Add 8mm diameter copper wire (copper purity ≥ 99.95%), 98% sulfuric acid, pure water, etc. into the copper dissolving tank;

[0066] (2) Adjust the required ion concentrations of the electrolyte in the clean liquid tank: copper ion 79g / L, H 2 SO 4 The concentration is controlled at 133g / L, and the chloride ion concentration is controlled at 11ppm;

[0067] (3) Add hydroxyethyl cellulose, collagen (molecular weight 3000D), and 2 kg of wood powder activated carbon into the waste liquid tank and circulate for 2 h;

[0068] (4) injecting the electrolyte into the electrolytic cell with the cathode roller through the liquid separator valve, introducing the prepared hydroxyethyl cellulose aqueous solution with a concentration of 1.0 g / L and adjusting the flow rate to 11 L / h; the concentration of the collagen aqueous solution was 1.5 g / L and adjusting the flow rate to 8 L / h;

[0069] (5) Use a plate heat exchanger to adjust and maintain the temperature of the upper liquid to 51°C; at the same time, adjust the upper liquid flow rate to 42m / s by controlling the upper liquid valve. 3 / h level;

[0070] (6) Use a polishing brush with a mesh size of 1200 to polish the surface of the cathode roller online, set the polishing brush speed to 190 r / min, the swing speed to 160±30 times / min, the polishing current to 0.3 A, the cathode roller speed to 1.100 m / min, and the polishing time to 70 min;

[0071] (7) After polishing, the current intensity is adjusted to 50000A and the cathode roller speed is adjusted to 5.083m / min for electrolysis;

[0072] (8) After electrolysis is completed, the electrolytic copper foil is peeled off from the cathode roller by a stripping roller after pickling.

[0073] The data of the electrolytic copper foil prepared in this example are shown in Table 1.

[0074] Example 4

[0075] (1) Add 8mm diameter copper wire (copper purity ≥ 99.95%), 98% sulfuric acid, pure water, etc. into the copper dissolving tank;

[0076] (2) Adjust the required ion concentrations of the electrolyte in the clean liquid tank: copper ion 84g / L, H 2 SO 4 The concentration is controlled at 126g / L, and the chloride ion concentration is controlled at 8ppm;

[0077] (3) Add hydroxyethyl cellulose, collagen (molecular weight 3000D), and 2 kg of wood powder activated carbon into the waste liquid tank and circulate for 2 h;

[0078] (4) injecting the electrolyte into the electrolytic cell with the cathode roller through the liquid separation valve, introducing the prepared hydroxyethyl cellulose aqueous solution with a concentration of 1.0 g / L and adjusting the flow rate to 10 L / h; introducing the collagen aqueous solution with a concentration of 1.5 g / L and adjusting the flow rate to 6 L / h;

[0079] (5) Use a plate heat exchanger to adjust and maintain the temperature of the upper liquid to 48°C; at the same time, adjust the upper liquid flow rate to 43m / s by controlling the upper liquid valve. 3 / h level;

[0080] (6) Use a polishing brush with a mesh size of 1200 to polish the surface of the cathode roller online, set the polishing brush speed to 250 r / min, the swing speed to 160±30 times / min, the polishing current to 0.3 A, the cathode roller speed to 1.100 m / min, and the polishing time to 55 min;

[0081] (7) After polishing, the current intensity is adjusted to 40000A and the cathode roller speed is adjusted to 4.196m / min for electrolysis;

[0082] (8) After electrolysis is completed, the electrolytic copper foil is peeled off from the cathode roller by a stripping roller after pickling.

[0083] The data of the electrolytic copper foil prepared in this example are shown in Table 1.

[0084] Example 5

[0085] The preparation process is basically the same as that in Example 1, except that in step (3):

[0086] Collagen with an equal mass molecular weight of 5000D was used.

[0087] Comparative Example 1

[0088] The preparation process is basically the same as that in Example 1, except that in step (4): the flow rate of hydroxyethyl cellulose is adjusted to 15 L / h (concentration remains unchanged), and the flow rate of collagen is adjusted to 11 L / h (concentration remains unchanged).

[0089] Comparative Example 2

[0090] The preparation process is basically the same as that in Example 1, except that in step (6):

[0091] The polishing time was changed to 40 min.

[0092] Comparative Example 3

[0093] The preparation process is basically the same as that in Example 1, except that in step (5):

[0094] The temperature of the supernatant was changed to 45°C.

[0095] Comparative Example 4

[0096] The preparation process is basically the same as that in Example 1, except that:

[0097] In step (5), the temperature of the upper liquid is changed to 53°C;

[0098] In step (6), the polishing time was replaced with 75 min.

[0099] Comparative Example 5

[0100] The preparation process is basically the same as that in Example 1, except that hydroxyethyl cellulose is not added in step (3).

[0101] Comparative Example 6

[0102] The preparation process is basically the same as that in Example 1, except that in step (3), hydroxyethyl cellulose is replaced by an equal mass of modified cellulose.

[0103] The copper foils prepared in each embodiment and comparative example were tested, wherein the tensile strength and elongation were tested using a universal material stripping machine and a universal material testing machine, respectively, and the matte surface roughness (MRz) and smooth surface roughness (SRz) were tested using a roughness meter. The specific values ​​are listed in Table 1 below.

[0104] Table 1

[0105] Sample No. <![CDATA[Tensile strength / N / mm 2 > Elongation % MRz(μm) SRz(μm) Control Standards ≥360 ≥6 ≤2.5 ≥1.3 Example 1 364 7 2.26 1.39 Example 2 362 8 2.43 1.40 Example 3 360 7 2.39 1.42 Example 4 364 7 2.32 1.32 Example 5 364 7 2.46 1.34 Comparative Example 1 357 7 2.57 1.32 Comparative Example 2 341 5 2.42 1.08 Comparative Example 3 349 6 2.69 1.32 Comparative Example 4 336 5 3.15 1.40 Comparative Example 5 338 5 3.33 1.38 Comparative Example 6 352 6 2.96 1.32

[0106] It can be seen from Table 1 that the electrolytic copper foils prepared in Examples 1 to 5 all meet the tensile strength requirement of ≥360 N / mm 2, elongation ≥ 6%, MRz ≤ 2.5 μm, SRz ≥ 1.3 μm, and can be used to prepare buried barrier copper foil, and Example 1 is the best example. However, the performance of the electrolytic copper foils prepared in Comparative Examples 1 to 6 does not meet the standards.

[0107] Figures 1 to 11 The SEM images of the copper foils prepared in Examples 1 to 5 and Comparative Examples 1 to 6 are shown in FIG. 1 . As can be seen from the drawings, the copper foils prepared in Examples 1 to 5 have dense and uniform copper nodules on the rough surface and a smooth structure as a whole, which is consistent with the data of lower roughness (MRz) of the rough surface; and the smooth surface has a strong smooth surface bite ability, which is also consistent with the data of higher smooth surface roughness (SRz).

[0108] Compared with the examples, the copper foils prepared in Comparative Examples 1, 3 to 6 have fewer copper nodules on the rough surface and uneven shapes. However, the copper foil prepared in Comparative Example 2 has weak bite ability on the smooth surface, which is not conducive to improving the corrosion resistance.

[0109] The above-mentioned embodiments are preferred embodiments, but the protection scope of the present invention is not limited thereto. A person skilled in the art can easily understand the spirit of the present invention based on the above-mentioned embodiments and make different extensions and changes. However, as long as they do not deviate from the spirit of the present invention, they are all within the protection scope of the present invention.

Claims

1. A production process for simultaneously improving the double-sided profile of copper foil, characterized in that: The following steps are involved: The copper sulfate electrolyte is injected into an electrolytic cell with a cathode roller, and then the prepared hydroxyethyl cellulose aqueous solution and collagen aqueous solution are injected into the electrolytic cell, and the copper foil is prepared after electrolysis; The concentration of the hydroxyethyl cellulose aqueous solution is 1.0±0.5 g / L, and the injection flow rate is 11±2 L / h; The concentration of the collagen aqueous solution is 1.5±0.5 g / L, and the injection flow rate is 8±2 L / h; Before electrolysis, the cathode roller is polished online for 45 to 70 minutes.

2. The production process for simultaneously improving the double-sided profile of copper foil according to claim 1, characterized in that: In the copper sulfate electrolyte, the copper ion concentration is 83.5±15 g / L, the H2SO4 concentration is 130±20 g / L, and the chloride ion concentration is 5-25 ppm.

3. The production process for simultaneously improving the double-sided profile of copper foil according to claim 1, characterized in that: The molecular weight of the collagen used in the collagen aqueous solution is not higher than 5000D.

4. The production process for simultaneously improving the double-sided profile of copper foil according to claim 1, characterized in that: The online polishing process is performed using a polishing brush; The mesh number of the polishing brush is 1200±500 mesh, the rotation speed is 220±30r / min, and the swing speed is 160±30 times / min; The pressure current of online polishing is 0.4±0.3A, and the rotation speed of the cathode roller is 2.2±0.5m / min.

5. The production process for simultaneously improving the double-sided profile of copper foil according to claim 1, characterized in that: The electrolysis: The upper liquid temperature is 51±3℃, and the upper liquid flow rate is 43±5m 3 / h; The current intensity is 45000±5000A, and the cathode roller speed is 4.721±0.7m / min.

6. A copper foil prepared according to the process according to any one of claims 1 to 5, characterized in that: The copper foil has a tensile strength of ≥360N / mm 2 , elongation ≥ 6%, MRz ≤ 2.5μm, SRz ≥ 1.3μm.

7. Use of the copper foil according to claim 6 in preparing buried barrier copper foil.

8. Application of the buried copper foil according to claim 7 in PCB.

Citation Information

Patent Citations

  • Low warp electrolytic copper foil for secondary battery and manufacturing method

    CN111485260A

  • Electrolyte for improving uniformity of particles on M surface of electrolytic copper foil, production process and product

    CN114032586A

  • Preparation method of electrolyte and production process of copper foil

    CN117684224A

  • Layered structure

    KR1020240022403A